(untitled) (Anwer Khan Modern Medical College Journal, 2022)
Background: Monitoring of antimicrobial resistance at local level is a very crucial aspect for clinical decision making, infection control interventions and antimicrobial-resistance containment strategies in this era of rising superbugs. The hospital antibiogram constructed by standardized method is a summary of antimicrobial susceptibilities of local bacterial isolates, with periodic review. Methods: This is a prospective observational study conducted in Microbiology Laboratory of Anwer Khan Modern Medical College Hospital (AKMMCH) over a period of three months from January to March 2021. All the samples which were received in the microbiology laboratory for aerobic bacterial culture and antibiotic sensitivity testing were considered in this study. The bacterial isolates from diagnostic clinical samples were subjected to culture in appropriate media for isolation of pathogens by standard methods and antibiotic sensitivity test (AST) was performed according to CLSI guidelines by modified Kirby Bauer disk diffusion techniques. Results: A total of 2917 samples were analysed in the microbiology department of AKMMCH for a period of three months of which 513(17.59%) were culture positive.Among the cultured samples of urine, respiratory sample, blood and pus, wound swabs, the rate of bacterial isolation was 266 (51.85%) ,161 (31.38%), 31 (6.04%) and 33 (6.4%) respectively. Most of the clinical isolates were Gram-negative bacilli404 (78.75%). The predominant isolate was Escherichia coli 186(36.26%) followed by Pseudomonas spp 102 (19.88%), Klebsiellaspp 79 (15.4%) and S. aureus 66 (12.87%). Antibiotic sensitivity in case of Gram-negative bacteria ranges from 30%-61% to amoxicillin-clavulanic acid, 18%-94% to third generation cephalosporin, 47%-75% to aminoglycosides, 27% -70% to ciprofloxacin, 26-70% to cotrimoxazole, 33-73% to nitrofurantoin, 27-69% to piperacillin- tazobactam and 100% to colistin. However, 53% of Escherichia coli and 58% of Klebsiella spp. were resistant to 3rd generation cephalosporins due to extended-spectrum beta-lactamase (ESBL) production. The carbapenem resistance in Escherichia coli was found 12%, Klebsiella spp 26%, Pseudomonas spp 29% and highest in Acinetobacter 46%. No superbug was detected in this study period. Conclusions: Antimicrobial susceptibility of various pathogen for different antibiotic is variable. Prompt antimicrobial therapy in an infection makes a lot of difference between recovery and death and most of the time prevents long term disability. Hence, antibiotic policy is one of the mandatory requirements and making an antibiogram is the first step before framing antibiotic policy. AKMMC J 2021; 12(2): 70-75